2021
DOI: 10.3390/nano11020320
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Thermophysical and Rheological Properties of Mxene Ionanofluids for Hybrid Solar Photovoltaic/Thermal Systems

Abstract: Since technology progresses, the need to optimize the thermal system’s heat transfer efficiency is continuously confronted by researchers. A primary constraint in the production of heat transfer fluids needed for ultra-high performance was its intrinsic poor heat transfer properties. MXene, a novel 2D nanoparticle possessing fascinating properties has emerged recently as a potential heat dissipative solute in nanofluids. In this research, 2D MXenes (Ti3C2) are synthesized via chemical etching and blended with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 51 publications
4
24
0
Order By: Relevance
“…It can be seen that NEILs exhibited superior dispersion stability in Figure 2D even after multiple experiments consisting of heating and cooling periods. The results of the previous researchers also indicated exceptional thermal stability in their studies 67 . Besides, the decomposition temperature of the ionic liquids is superiorly high compared to the conventional working fluids.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…It can be seen that NEILs exhibited superior dispersion stability in Figure 2D even after multiple experiments consisting of heating and cooling periods. The results of the previous researchers also indicated exceptional thermal stability in their studies 67 . Besides, the decomposition temperature of the ionic liquids is superiorly high compared to the conventional working fluids.…”
Section: Resultsmentioning
confidence: 86%
“…The results of the previous researchers also indicated exceptional thermal stability in their studies. 67 Besides, the decomposition temperature of the ionic liquids is superiorly high compared to the conventional working fluids. It was reported in the study of Cao et al 68 The measured thermal conductivity of various HMIM cation-based MWCNT NEILs and pure RTILs is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In general, increase in volume fraction of nanostructures causes increase in both viscosity and thermal conductivity [9,10]. Despite the advantages of high thermal conductivity for heat transfer purposes, the increase in dynamic viscosity is unfavorable; consequently, there is an optimum concentration in the majority of the cases [11,12]. In comparison with specific heat capacity of nanofluids, more attentions have been attracted by dynamic viscosity and thermal conductivity; however, several studies have focused on this property of the nanofluids due to its substantial role in heat transfer of operating fluids.…”
Section: Introductionmentioning
confidence: 99%
“…There is little literature on the influence of ultrasound treatment conditions on the microstructure as well as thermal and rheological properties of INFs. Most of the research in the field was carried out under constant sonication settings [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . The notable exceptions were works of Wittmar et al [32] , [33] , who investigated rheological properties of INFs containing 0.5 wt% 95% anatase TiO 2 with average particle size 5 nm or 100% anatase TiO 2 with average particle size from 5 to 26.4 nm and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [Emim][NTf 2 ], 1-ethyl-3-methylimidazolium tetrafluoroborate [Emim][BF 4 ], 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF 4 ], or 1-hexyl-3-methylimidazolium tetrafluoroborate [Hmim][BF 4 ], prepared with various sonication times up to 4 h. They concluded that the rheological behavior of nanodispersions was complex and depended on the type of IL.…”
Section: Introductionmentioning
confidence: 99%